2021
DOI: 10.1038/s41598-021-86625-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of phonemic fluency following leftward prism adaptation

Abstract: Anatomo functional studies of prism adaptation (PA) have been shown to modulate a brain frontal-parieto-temporal network, increasing activation of this network in the hemisphere ipsilateral to the side of prism deviation. This effect raises the hypothesis that left prism adaptation, modulating frontal areas of the left hemisphere, could modify subjects’ performance on linguistic tasks that map on those areas. To test this hypothesis, 51 healthy subjects participated in experiments in which leftward or rightwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The recent report on the modulation of linguistic functions following left hemispheric activation via spatial adaptation procedures [18] also aligns with the model of interaction between spatial attention and language in the left hemisphere.…”
Section: Discussionsupporting
confidence: 76%
“…The recent report on the modulation of linguistic functions following left hemispheric activation via spatial adaptation procedures [18] also aligns with the model of interaction between spatial attention and language in the left hemisphere.…”
Section: Discussionsupporting
confidence: 76%
“…This is further supported by the evidence that in both patients with neglect as well as in healthy individuals, different lines of evidence support that PA enhances visual search abilities 54 , orienting of attention 55 57 , and spatial/temporal representations of stimuli 58 60 . More specifically, rightward-deviating lenses have shown to strengthen the activation of brain attentional networks 61 63 , while leftward-deviating lenses to improve phonological skills 64 . Moreover, unlike other complex visual stimulation techniques requiring extended exposure, adaptation to prisms quickly develops over the course of a 5-min simple pointing session 65 , 66 , thus ensuring good affordability and tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the beneficial effects of PA on various populations including healthy individuals ( Bonaventura et al, 2020 ; Turriziani et al, 2021 ; Magnani et al, 2022 ), psychiatric populations ( Magnani et al, 2022 ), and neurological populations, particularly those suffering from USN ( Shiraishi et al, 2008 ; Serino et al, 2009 ) characterized by an improvement in daily activities such as reading, writing, and wheelchair navigation ( Dijkerman et al, 2003 ; Angeli et al, 2004a , b ; Rode et al, 2006 ; Jacquin-Courtois et al, 2008 ; Watanabe and Amimoto, 2010 ). Furthermore, PA based-rehabilitation has been shown to reduce deficits in various domains, including neglect ( Rossetti et al, 1998 ; Làdavas et al, 2001 ; Dijkerman et al, 2003 ; Maravita et al, 2003 ; Jacquin-Courtois et al, 2010 ), visuospatial ( Farnè, 2002 ) and postural deficits ( Tilikete et al, 2001 ; Hugues et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%